A qualidade da educação na Rede Municipal de Ensino de São Paulo: o desempenho em língua portuguesa e as condições objetivas para a formação dos alunos - Rossetto, Alessandra Colombo (2011)
This study aims at assessing the conditions in which the education and training of students who are part of the Municipal Education System takes place according to two basic premises: the first being that the spaces and the material resources available may (positively or negatively) influence the students performance regarding the studying of the Portuguese Language and the second being that this influence, when present, may vary according to the IEX of the different regions of the city of São Paulo. In order to accomplish such assessment, the quality of the education, the education evaluation and the presence of a reading room were taken into consideration. The core question in which this study was build upon is: In which conditions education and training occur in the Municipal Education System of São Paulo considering the use of spaces and specific resources available at the schools when writing and reading skills are taught? The analyses carried out in this study are based upon the critical theory of society, mainly on some of the contributions of Theodor Adorno, Walter Benjamin and Herbert Marcuse who allowed the further understanding of the concepts of formation, experience and ideology of technological rationality. Our findings show that students from schools located in more socially included regions are more adapted to the standards established as necessary in the current society and, therefore, students from schools located in regions with a lower IEX are less adapted to the rules of the capitalism. Moreover, regardless of the location of the school and the specific reading resources available, the learning process occurs in a noncritical way and the students get in touch with the syllabus in a fragmented and superficial way